Derecho y evolución: la naturaleza humana y la función adaptativa del comportamiento normativo - Fernandez, Atahualpa (Nómadas. Critical Journal of Social and Juridical Sciences, 2005)
The objective this article is to offer a critical (re)interpretation of genesis and evolution, object and purpose, as well as useful qualified methods for interpreting, justifying and applying modern practical law, all with the intention of putting philosophic thought and contemporary formal theory of reason at the service of hermeutics and juridical argumentation. Law is no more—no less—than an adaptive strategy, evermore complex, but always noticeably deficient, used to articulate argumentatively—in fact, not always with justice—through the virtue of prudence, elementary relational social ties through which men construct approved styles of interaction and social structure, i.e., to organize and ethically improve political and social life in such a way as to permit that no free citizen—rich or poor—should fear the arbitrary interference of other social actors in his life plan.